Digital Media, Generations and Transforming Social Relationships - SİLİ KALEM, Ayşegül (Cyberpolitik Journal, 2021)
Today, internet and associated digital media continues to be indispensable in our every day life. Replacement of traditional media with electronic/digital media just before the 21st century led to a radical change in a wide range of areas in our lives from socializing and communication styles to daily activities, from marketing to health as well as morals and privacy. This especially shows itself in the generation after the year 2000 with their immaculate adaptability to technology which opened the gates to a lifestyle which deems the old as outdated and formed prominent differences from the generations before them. This new world in which technology is the dominant factor brings forth a series of phenomena and issues not only in the physical and environmental sense but also in the re- formation of social and mental structures. This study intends to discuss the effects of digital media on the society through generation Z. Contrary to generations who acquired the skills of technology later in life, generation Z, along with all the differences in their lifestyles and perceptions, have already taken their places as the founding actors, and as “digital natives” of the brand new world.